Online certificate injection system - Samsun Baharun, Mohd. Nor Haizam (2005)
Identity is your most valuable commodity on the Internet or online transaction. It defines who you are and is essential in doing business and carrying personal information over the net. Unfortunately on the Internet, identity can be ambiguous. The online users can now protect themselves with the use of Digital Certificate which is using a cryptographic system. A cryptographic system that uses two keys - a public key is known to everyone and a private or secret key only known to the recipient of the message. An important element to the public key system is that the public and private keys are related in such a way that only the public key can be used to encrypt messages and only the corresponding private key can be used to decrypt them. Moreover, it is virtually impossible to deduce the private key if you know the public key. OCIS was developed to request the certificate from CCM Server and then inject the certificate into the smart card. The smart card contains two certificate .i.e. Digital Signature Certificate and Non- Repudiation Certificate and can be used to make a secured online transaction.